Effects of a physical activity promotion program over adolescent women from two schools in bogotá, D.C. (2016)
Introduction: Physical inactivity currently prevails throughout the population, particularly adolescents, generating health consequences. In turn, the school setting provides a conducive environment to promote healthy lifestyles. This study proposes the implementation and evaluation of the impact of a model for physical activity promotion, with the purpose of modifying individual and collective behaviors towards regular physical activity. Objective: To assess the effects of a physical activity promotion program on fitness components related to health in adolescent women from two schools in Bogotá. Materials and methods: This is a longitudinal, descriptive, exploratory study with pre-post fitness measurements related to health. 49 healthy female students from two schools in Bogota (aged15.33±1.36) participated in the program for 12 weeks. SPSS 20 was used for analysis. Results: After the intervention, significant changes were found in abdominal and lower limb strength. Other variables measured showed positive changes, but not significant. Conclusions: The proposed program generates positive changes in most fitness components regarding health in adolescent women. © 2016, Universidad Nacional de Colombia. All rights reserved.